Analisis Kemampuan Penggunaan Isim Isyarah (Kata Tunjuk) dalam Pembelajaran Bahasa Arab - Indah Puspa Pertiwi; Muhammad Wisnu Khumaidi; Muhammad Zaky Sya’bani (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2021)
This reasearch was conducted because there are still difficulities on learning Arabic, especially in the use of pointing words (isim isyarah). In theory, the stundents are able to mention pointing words (isim isyarah), but some errors were still found when the written test was carried out, among which students still having difficulty to understanding the material about pointing words (isim isyarah) so it is difficulty to distinguish pointing words based on amount and type. This study aims to know the ability of students in the use of pointing words (isim isyarah) on learning Arabic and to find out factors that affect Arabic language skills, especially in the use of pointing words (isim isyarah) on learning Arabic for class VIII G MTs Darul Huffaz Pesawaran. This type of reasearch is descriptive research with qualitative approach and this research was conducted at MTs Darul Huffaz Pesawaran. Method of collecting data use are interviews, observation, test, questionnaires, and documentation. And the result showed that the understanding level of class VIII G in the use of pointing words (isim isyarah) was still too low, this is also influenced by internal factors, physical health when attending learning in the class and shyness in asking questions, it can be seen from the gesture of students when the lessons on progessing, students don’t try to ask questions related to material that they don’t understand, and external factors are method used by teacher which is used continously and maybe it can be boring for students, and the use of learning media, Arabic teacher only use them such as LCD proyektor occasionally.